DEFORMATION CHANGES IN THE FAMENNIAN-TOURNAISSIAN CARBONATE ROCKS IN THE NORTHWESTERN MARGINAL FAULT ZONE OF THE CASPIAN BASIN - V. V. Korobkin; Zh. S. Tulemissova; A. E. Chaklikov (Геодинамика и тектонофизика)
The Northwestern marginal fault zone is a part of the Caspian Basin and a boundary transition structure separating the basin from the Volga-Ural region. It has been found that this fault zone is characterized by a complex kinematic development leading to the formation of a linear salt-dome structure. Research has been carried out on deformation changes in the Famennian-Tournaisian carbonate rocks in the Northwestern marginal fault zone. A set of macro- and microscopic studies made it possible to assess the nature of deformation changes, the state of structural and textural maturity, the composition of the original rocks, as well as to identify the composition of secondary minerals and void space and determine the kinematic types of tectonic fractures formed therein. The recognition of carbonate mineralogical varieties has been performed by the method of thin section staining with alizarin red, which made it possible to distinguish between calcite and dolomite and to determine their quantitative ratio in thin sections. The carbonate samples were studied by X-ray diffraction, and thermal and probe methods, which revealed the features of the crystalline phase and accessory impurities and provided a characterization of the crystalline structure of minerals. Analytical studies made it possible to identify thermally inert formations of calcium, magnesium, silicon and iron oxides and other compounds in carbonates and to determine the nature of deformation changes in the Famennian-Tournaisian carbonate reservoir rocks.